Patients’ perspectives on the extent of resident participation in the operating room for total hip or knee arthroplasty - Bryce, Jessica; Ndoja, Silvio; Goyal, Prateek; Lanting, Brent; Howard, James (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2021)
Introduction: Previous work suggests that patients do not understand the extent of trainee involvement in their care and are uncomfortable with trainee involvement.Methods: We recruited 202 English speaking patients with previous or planned total joint arthroplasty of the lower limb for a prospective survey trial. We assessed participant’s knowledge of trainee level of education and confidence of trainee involvement in their surgery as a function of supervision.Results: Participants’ mean level of confidence in the consultant surgeon was 4.30 (SD±1.13) on a 5-point Likert scale. Confidence in residents was significantly less, regardless of resident experience (p < 0.05). 11.1% of participants did not want trainees involved in their treatment.  60.6% would like to know more about the education level of the trainee. Less than half of participants correctly identified the education level of residents and fellows.Conclusion: Patient confidence in trainees performing part or all of their surgery increases with resident experience and supervision. Most patients do not understand the hierarchy in education of medical trainees and would like to know more about the education level of the trainee involved in their care. Further work should explore how we can help patients better understand trainee involvement in their surgical care.